ANALISIS KOMPONEN KIMIA MINYAK KAYU CENDANA DENGAN KROMATOGRAFI GAS - Abdul Hakim Lukman; Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1988)
The purpose of  this research is to identify  chemical  components of sandalwood  oil by using the gas chromatography method. This sandalwood  oil  was  obtained   by  steam  and  water  distillation  for 18,  24,  and  30  hours  distilling  times. The  condition  of  the  gas chromatography   employed  was adjusted to :  injector  temperature  200°  C. detector temperature 0°  C,  initial  column   temperature  140°  C,  final  temperature  column  200°  C, speed  temperature   column   5° C/min,   with nitrogen  gas as carrier, and  the  using  the  flame  ionization   detector  system.    The identification  of  the peak  components was done  by  comparing  the  relative retention   time  of  the peak  component   with  the peak  retention   time  chemical  solution standard.   The peak  area of  each components    was calculated  by  normalization   method.The  results  indicated   that  chemical components of  sandalwood oil, which  was produced   by  the  steam  and  water distillation   for  18, 24,  and  30  hours,  include  0.0391, 0.0271, and  0.0313 % of α-pinene;  0.0065,  0.0034, and  0.0027 % of  limonene;  0.9147,  0.7799,   and  1.0393   % of α-santalene; 2.4375,1.9802, and 2.3474  % of  terpineol 4;  1.2184, 0.7922, and  0. 7921 % of  β-santalene;   5. 7263,  3.8800, and 3.9335  % of nerolidol; 48.0481, 51.1802. and 50.3507 % of β-santalol; 22.4367,  24.7127, and  24,2864 % of  (arnesol, Unidentified   component  in each distilling time were  19.1727,15.6443, and  17.2166   %. respectively.    The β -santalol  component    occupies  the  mayor  component   of  sandalwood   oil.  The  amount of  this component  at each  treating  condition was 48.0481 % for 18  hours;  51.1802 % for 24 hours; and 50.3507  % for 30 hours. Terpineol-4, nerolidol, β-santalol.   and  farnesol  components  constitute   the sandalwood   oil and is usually  calculated as the  total  santalol.